Novel perspectives on antisense transcription in HIV-1, HTLV-1, and HTLV-2 - Lin, Edward; Panfil, Amanda R.; Sandel, Grace; Jain, Pooja (Frontiers in Microbiology, 2022)
The genome of retroviruses contains two promoter elements (called long terminal repeat or LTR) at the 5’ and 3’ end of their genome. Although the expression of retroviral genes generally depends on the promoter located in the 5’ LTR, the 3’ LTR also has promoter activity responsible for producing antisense transcripts. These natural antisense transcripts (NATs) are a class of RNA molecules transcribed from the opposite strand of a protein-coding gene. NATs have been identified in many prokaryotic and eukaryotic systems, as well as in human retroviruses such as human immunodeficiency virus type 1 (HIV-1) and HTLV-1/2 (human T-cell leukemia virus type 1/2). The antisense transcripts of HIV-1, HTLV-1, and HTLV-2 have been briefly characterized over the past several years. However, a complete appreciation of the role these transcripts play in the virus lifecycle and the cellular factors which regulate their transcription is still lacking. This review provides an overview of antisense transcription in human retroviruses with a specific focus on the MEF-2 family of transcription factors, the function(s) of the antisense protein products, and the application of antisense transcription models in therapeutics against HIV-1 and HTLV-1 in the context of co-infection.